FACTORS OF THE MANIFESTATION OF PROFESSIONAL BURNOUT AND EFFICIENCY OF TEACHERS IN ONLINE LEARNING - Mirzoyan , V. Kh.; Mikaelyan, M. Yu. (Modern Psychology, 2022)
Professional activity plays a huge role and significance in a person's life. It contributes to the knowledge enrichment, skill development, and provides personal and professional growth. At the same time, professional activity can harm a person's physical and mental health and cause professional burnout. Employees in the education system, particularly teachers, have encountered a number of psychological problems as a result of transition to distance learning in connection with COVID-19. Online- learning became a catalyst that has accelerated the onset and progression of psychophysical symptoms. The lack of direct interpersonal communication, the emotional connection, the existence of various technical problems, a low level of computer competence, inability to use online tools, isolation and constant fear led to body exhaustion and decreased performance. This was especially noticeable among the teachers working in urban schools. The article discusses the causes of professional burnout and its manifestations. Professional burnout is harmful not only to a particular person, but also to society as a whole. The article presents psychological factors that affect working capacity, as well as the relationship between professional working capacity and professional burnout. A study was conducted with 280 teachers from urban and rural schools, which resulted in a decrease in working capacity and the existence of professional burnout, and it was revealed that the indicators in two methods are almost double for urban school teachers.
Keywords: professional burnout; performance; professional performance; online training